Electrophysiological characteristics of right- and left-sided Mahaim accessory pathways: A single-center experience in China - Chen, Mingxian; Wang, Zhuo; Wang, Songyun; Liu, Zhenjiang; Li, Xuping; Yang, Hui; Hu, Lin; Wu, Zhihong; Li, Qiming; Zhou, Shenghua (Frontiers in Cardiovascular Medicine, 2022)
Background: Mahaim accessory pathway (MAP) are rare accessory pathways (AP) with specific properties. They mostly locate in right side of the heart, but rarely exist in left side. Objectives: The present study aims to analyze the clinical and electrophysiological characteristics of both-sided MFs. Methods: A total of 2249 patients with AP from our center were enrolled between January 1, 2011 and March 27, 2022. 17 patients were diagnosed as MAPs (right-sided n=13, left-side n=4) according to the Mahaim fibers properties during the electrophysiological study (EPS). Results: Mahaim-type Aps constitute 0.75% of all APs. Out of 1553 patients with left-sided APs, 4 patients (0.26%) were diagnosed as Mahaim fiber-mediated tachycardia. Out of 696 patients with right-sided APs, 13 patients (1.9%) were diagnosed as Mahaim fiber. Most Mahaim fibers were located at the free wall of tricuspid and mitral annulus. 7 right-sided patients were atriofasicular MAPs. 6 right-sided patients and all of the left-sided patients were atrioventricular MAPs. M potential only was detected in long length MAPs. Coexistence with other SVTs were also observed both in patients with right-sided and left-sided MAPs. All the patients underwent radiofrequency ablation successfully. Only one patient had tachycardia recurrence during follow-up. Conclusion: Although MAPs are commonly located at tricuspid annulus, left-sided are not impossible. M potential contributes to improvement of the successful ablation.